1997
DOI: 10.1111/j.1601-0825.1997.tb00037.x
|View full text |Cite
|
Sign up to set email alerts
|

External resorption presenting as an intracoronal radiolucent lesion in a pre‐eruptive tooth

Abstract: A large intracoronal radiolucent lesion in an unerupted permanent molar was found during the routine assessment of a young male Caucasian prior to orthodontic treatment. The tooth was extracted. Histological examination indicated the lesion was caused by external resorption. The defect extended widely into the enamel and dentine, and was repaired in part by bone. The pulp chamber was not involved. The aetiology of these lesions is often obscure but in this case it appeared to have originated in the floor of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 6 publications
0
33
0
4
Order By: Relevance
“…As the radiographic appearance of the radiolucency is similar to that of dental caries, they were often referred to as ''pre-eruptive caries'' in earlier literature [4]. Recently, many case reports have provided clinical and histological evidence that these lesions are likely to be resorptive in nature [3,[5][6][7][8][9][10][11][12][13], and the term ''pre-eruptive intracoronal resorption or defect'' is now preferred [3,6,11,14,15]. Clinical symptoms of these lesions are usually minimal or absent, and are characteristically noted as incidental findings on routine dental radiographs of unerupted teeth [1-3, 9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…As the radiographic appearance of the radiolucency is similar to that of dental caries, they were often referred to as ''pre-eruptive caries'' in earlier literature [4]. Recently, many case reports have provided clinical and histological evidence that these lesions are likely to be resorptive in nature [3,[5][6][7][8][9][10][11][12][13], and the term ''pre-eruptive intracoronal resorption or defect'' is now preferred [3,6,11,14,15]. Clinical symptoms of these lesions are usually minimal or absent, and are characteristically noted as incidental findings on routine dental radiographs of unerupted teeth [1-3, 9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…4 In some studies, extraction of teeth was also reported due to extensive resorption. 11,18 Moskovits and Holan 3 waited for the tooth to erupt; they began the treatment when the patient complained about sensitivity of the tooth. In our case, we began treatment before the patient complained.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of this layer can result in connective tissue coming into direct contact with the enamel. 17,18 Chronic periodontal inflammation may promote epithelial disruption and osteoclastic activity.…”
Section: Discussionmentioning
confidence: 99%
“…2,13,16 Preerüptif intrakoronal rezorpsiyona ait histolojik incelemelerde, dentin dokusu içinde rezorptif hücrelere (makrofaj, osteoklast ve çok çekirdekli dev hücreler) rastlanmıştır. 19 Sürmemiş diş çevresinde yer alan mine epitelinin azalması ve bütünlüğünün bozulması nedeni ile meydana gelen defektlerin, dişlerin ektopik pozisyonu veya komşu dişin neden olabileceği baskı gibi lokal faktörlerin rezorptif hücreleri aktive edebileceği ve bu hücrelerin mine-sement birleşiminden veya minedeki fissürlerden dentine doğru ilerleyip intrakoronal rezorpsiyona neden olabileceği bildirilmiştir. 12,16,[19][20][21] Preerüptif intrakoronal rezorpsiyonun tedavisi için yaklaşımlar, araştırmacılara ve lezyonun büyüklüğüne göre çeşitlilikler göstermektedir.…”
unclassified
“…19 Sürmemiş diş çevresinde yer alan mine epitelinin azalması ve bütünlüğünün bozulması nedeni ile meydana gelen defektlerin, dişlerin ektopik pozisyonu veya komşu dişin neden olabileceği baskı gibi lokal faktörlerin rezorptif hücreleri aktive edebileceği ve bu hücrelerin mine-sement birleşiminden veya minedeki fissürlerden dentine doğru ilerleyip intrakoronal rezorpsiyona neden olabileceği bildirilmiştir. 12,16,[19][20][21] Preerüptif intrakoronal rezorpsiyonun tedavisi için yaklaşımlar, araştırmacılara ve lezyonun büyüklüğüne göre çeşitlilikler göstermektedir. 22 Küçük lezyonlarda radyografik izlem, ilerlemiş lezyonlarda ise dişin cerrahi operasyon ile açığa çıkarılarak temizlenmesi önerilmektedir.…”
unclassified